Influence of Acid Modification Multiwall Carbon Nanotube Counter Electrodes on the Glass and Flexible Dye-Sensitized Solar Cell Performance - Wasan Maiaugree; Samuk Pimanpang; Wirat Jarernboon; Vittaya Amornkitbamrung (International Journal of Photoenergy)
Multiwall carbon nanotubes (MWCNTs) were modified by acids (H2SO4 : HNO3) for generating active groups on the nanotube surface. Unmodified- and modified-carbon nanotubes were coated on the conductive glass and conductive plastic substrates by a slurry paste method, and they were used as the counter electrodes (CEs) of dye-sensitized solar cells (DSSCs). Scanning electron microscopy reveals that carbon nanotubes are evenly deposited on the conductive glass. The efficiency of the glass based DSSCs of unmodified- and modified-carbon nanotubes and Pt CEs is ~4.73%, ~5.66%, and ~6.08%, respectively. The efficiency of the plastic based DSSCs of the unmodified- and modified-carbon nanotubes CEs is ~0.80% and ~2.11%, respectively. The voltammogram and electrochemical impedance spectroscopy results suggest that the superior performance of the modified-carbon nanotubes DSSCs is attributable to the high electrocatalytic activity and the low charge-transfer resistance of the modified-carbon nanotubes film over the unmodified-carbon nanotubes film.